Effects of reduced application of special organic fertilizers on tea production (Bangladesh Journal of Botany, 2021)
A trial of special fertilizer reduction and combined application of organic fertilizer on tea production, nutrients and economic benefits was carried out in the tea garden at Shihe Port, Xinyang, Henan Province, China. The experiment has six treatments of customary fertilization (CK), 100% special fertilizer for tea (T1), nitrogen reduction 20% (T2), 40% (T3), 60% (T4) and 100% (T5), and special fertilizers at the same time. Among the special fertilizer treatments for tea plants, the germination density, 100-bud weight, fresh tea yield, N, P, and K content of new shoots and economic benefits were the highest in T1 treatment, Results showed that the yield range of the five treatments was 460～632.4kg hm2. Compared with CK, the yield increase rates were 6.11, 1.99, -4.21, -13.76 and -22.82%, respectively. The growth rates of barber bud density and 100-bud weight were -20.00～25.83 and 8.40～ 8.40%, respectively. The content of nitrogen, phosphorus and potassium in the new shoots varied by 0.623～1.070, 0.047～0.183 and 1.380～2.237%, respectively. Therefore, the special fertilizer for tea plants can reduce the nitrogen by 20% to save costs and increase efficiency.Bangladesh J. Bot. 50(3): 939-945, 2021 (September) Special